Marah Labid by Shaykh Nawawi al-Bantani: A Methodological Bridge between Traditional and Early Modern Qur’anic Exegesis - El-Karimah, Mia Fitriah; Fuadah, Siti; Istianah, Siti; Kurnia, Rina (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) ZAD, 2025)
This study examines Tafsir Marah Labid by Sheikh Nawawi al-Bantani as a methodological bridge between traditional and modern Qur'anic interpretation. Using qualitative methods with tahqiq approach and manuscript analysis, this research reveals that Marah Labid uniquely integrates ijmali (global), tahlili (analytical), and muqaranah (comparative) techniques while combining bi al-ma'tsur (traditional sources) and bi al-ra'y (independent reasoning). The tafsir enriches interpretation through linguistic analysis, asbab al-nuzul, qira'at, and isyari (sufistic) dimensions. Despite minor weaknesses such as uncritical inclusion of Israiliyyat narratives, this work has served as a foundational text in Indonesian pesantren curricula, shaping moderate Islamic scholarship and demonstrating continued relevance for contemporary Muslim communities. This study fills a methodological gap by comprehensively analyzing Nawawi's interpretive techniques and their contribution to Nusantara exegetical heritage.